ANALISIS KEBIJAKAN FISKAL DAERAH: KAJIAN TERHADAP PERDA KOTA PADANG PANJANG NOMOR 4 TAHUN 2023, PERDA NOMOR 1 TAHUN 2024, DAN PERDA NOMOR 3 TAHUN 2024 - Erizona, Wawan; Frinaldi, Aldri; Asnil, Asnil; Putri, Nora Eka (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the direction, effectiveness, and continuity of the fiscal policy of the Padang Panjang City Government as regulated in three main legal instruments: Regional Regulation (Perda) Number 4 of 2023 on the 2024 Regional Budget (APBD), Perda Number 1 of 2024 on Regional Taxes and Levies, and Perda Number 3 of 2024 on the Amendment to the 2024 Regional Budget. This research employed a qualitative descriptive approach using document analysis and triangulation of recent academic literature. The findings reveal that the 2024 regional budget structure remains heavily dependent on central government transfers (81.8%), while locally generated revenue (PAD) contributes only 18.2%. However, the implementation of digital-based local tax policy under Perda Number 1 of 2024 and productive expenditure reallocation under Perda Number 3 of 2024 demonstrate a strong commitment to fiscal efficiency and transparency. The study concludes that Padang Panjang’s fiscal policy aligns with the principles of prudential fiscal management, though institutional capacity and financial digitalization need strengthening to achieve sustainable fiscal autonomy.